PENGARUH SOSIAL - BUDAYA DALAM PENAFSIRAN AL-QUR’AN KONTEMPORER - Mubhar, Muhammad Zulkarnain; Asriadi; Imam Zarkasyi Mubhar (LP2M IAIM Sinjai, 2025)
The interpretation of the Qur'an in the contemporary context cannot be separated from the influence of the social and cultural environment surrounding the interpreters. Different from the classical approach which tends to be textual and normative, contemporary interpretation is more open to the dynamics of modern society, including issues of gender, human rights, pluralism, and social change. This article aims to examine how socio-cultural factors influence the process and results of interpretation of the Qur'an by contemporary interpreters. Using qualitative methods based on literature studies and a hermeneutic approach, this study analyzes the works of several modern interpreters such as Fazlur Rahman, Amina Wadud, and Quraish Shihab. The findings show that social and cultural constructions play a significant role in shaping the perspective, choice of themes, and emphasis of meaning in the resulting interpretation. Interpretation is no longer understood as a single product of the text, but as a dynamic dialogue between the text, context, and interpreter. This article concludes that awareness of socio-cultural influences can open up space for more relevant, humanistic, and contextual interpretations in responding to the challenges of the times. This research is expected to contribute to the development of a more inclusive and reflective contemporary interpretation methodology.